Medical Students Knowledge and Attitude Towards Direct-To-Consumer Genetic Tests - Luca Giraldi; Marco Colotto; Roberta Pastorino; Dario Arzani; Effy Vayena; Christian Ineichen; Stefania Boccia (Epidemiology, Biostatistics and Public Health)
Aims: This study reports on the attitudes of 179 Italian Medical Students to direct-to-consumer genetic test and to participation in research practices.